Resting heart rate (variability) and cognition relationships reveal cognitively healthy individuals with pathological amyloid/tau ratio - Molloy, Cathleen; Choy, Elizabeth H.; Arechavala, Rebecca J.; Buennagel, David; Nolty, Anne; Spezzaferri, Mitchell R.; Sin, Caleb; Rising, Shant; Yu, Jeremy; Al-Ezzi, Abdulhakim; Kleinman, Michael T.; Kloner, Robert A.; et al. (Frontiers in Epidemiology, 2023)
Resting heart rate (HR) and heart rate variability (HRV) have been linked with cognition in the general population and in older individuals. The knowledge of this aspect of heart-brain relationship is relatively absent in older individuals with early Alzheimer’s disease (AD) pathology. This study explores relationships of the HR, HRV, and cognition in cognitively healthy individuals with pathological amyloid/tau ratio (CH-PATs) in cerebral spinal fluid (CSF) compared to those with normal ratio (CH-NATs). We examined the relationships between 1) resting HR and Mini‐Mental State Examination (MMSE); 2) resting HR and brain processing during Stroop interference; and 3) resting vagally mediated HRV (vmHRV) and task switching performance. Our studies showed that compared to CH-NATs, those CH-PATs with higher resting HR presented with lower MMSE, and less brain activation during interference processing. In addition, resting vmHRV was significantly correlated with task switching accuracy in CH-NATs, but not in CH-PATs. These three different tests indicate dysfunctional heart-brain connections in CH-PATs, suggesting a potential cardio-cerebral dysfunctional integration.